Ballet for Martha : making Appalachian Spring - Greenberg, Jan, 1942- (RB/Flash Point, 2010)
Tells the story behind the creation of "Appalachian Spring," describing Aaron Copland's composition, Martha Graham's intense choreography and Isamu Noguchi's set design.